Analysis of the NSC Storage Dynamics in Tree Organs Reveals the Allocation to Belowground Symbionts in the Framework of Whole Tree Carbon Balance - Schiestl-Aalto, Pauliina; Ryhti, Kira; Mäkelä, Annikki; Peltoniemi, Mikko; Bäck, Jaana; Kulmala, Liisa (Frontiers in Forests and Global Change, 2019)
Photosynthesis is not entirely synchronized with carbon sinks, implying that trees are capable of storing non-structural carbohydrates (NSC) such as soluble sugars and starch. These storages provide a buffer between carbohydrate supply and demand and also allow trees to resist drought through osmoregulation. However, estimates of the total pool size and seasonal dynamics of the NSC storage of mature trees are still rare. Part of NSC is allocated outside roots, mainly to symbiotic, root-associated mycorrhizal fungi. The quantity and dynamics of this allocation are difficult to estimate in field conditions due to the close interaction between the symbionts. The aims of this study were to (1) determine the temporal development of NSC concentrations in tree organs, (2) upscale the storage compounds to whole-tree level and (3) analyse the significance of NSC allocation to belowground symbionts as part of the carbon balance in mature pines in a boreal Scots pine stand in southern Finland. We took samples every 2–4 weeks of needles, fine roots, stem wood, shoot wood and phloem from 1–3 trees in 2015. Concentrations of soluble sugars and starch were analyzed from the samples and upscaled to tree level. For quantifying the third aim, we used a whole-tree carbon balance model CASSIA that incorporates daily photosynthesis, respiration and organ-specific growth as functions of environmental factors. In this study, we included the allocation to belowground symbionts as an additional carbon sink and scaled the flux using the NSC pool over the whole tree. We observed that organ-specific NSC concentrations were highest in phloem, needles and fine roots. Total NSC increased in spring, peaked during mid-summer and decreased again in autumn without any notable decrease during the most intensive growth period at midsummer. In the model analysis, 6 % of yearly photosynthesis was allocated to the root-associated symbionts. The study highlights the applicability of the carbon balance approach in evaluating the importance of processes that cannot yet be directly measured.